Pengaruh Kepuasan Pernikahan dan Self-Esteem pada Sikap Terhadap Perselingkuhan Dewasa Awal yang Bekerja: Penelitian - Izdihar Afra; Raras Sutatminingsih; Rodiatul Hasanah Siregar (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Infidelity is a common phenomenon in marriage and is now occurring frequently in workplace settings. This study aims to examine the effect of marital satisfaction and self-esteem on attitudes toward infidelity among working early adults. A quantitative approach with a causal associative research design was used. The respondents were 350 early adults aged 20–40 years. Data collection instruments included adapted versions of the Attitude towards Infidelity Scale (ATIS), the ENRICH Marital Satisfaction Scale (EMSS), and the Rosenberg Self- Esteem Scale (RSES). Data were analyzed using multiple linear regression. The results showed that marital satisfaction and self-esteem simultaneously had a significant effect on attitudes toward infidelity (p = 0.001) with a 19.7% contribution. Partially, marital satisfaction had a significant negative effect on attitudes toward infidelity (t = –0.239, p = 0.000), and self-esteem also had a significant negative effect (t = –0.330, p = 0.000). These findings indicate that both marital satisfaction and self-esteem serve as protective factors for attitudes toward infidelity.